Isotropic and orthotropic dynamics models of the tympanic membrane - Martínez Celorio, R A; Rodríguez Bravo, H; Rodríguez Cruz, R A; Martí López, L; Castro Sánchez, R; Ireta Moreno, F; Hernández Fusilier, D; Vega Corona, A; González Peña, R (Revista Mexicana de Ingenieria Biomedica, 2018)
In this paper, the isotropic and orthotropic models of the tympanic membrane (with and without hammer bone) are studied. The methodused in this paper is based on the finite element method. The tympanic membrane form was obtained by a digitalization of human tympani. This part of the ear was collected from a dead body. The process was performed with a XYZ «touching machine» interconnected to the so called coordinate machine. The finite element software may include the material properties that characterize each section of the tympanic membrane, the boundary conditions describing the contact between the tympanic membrane and the temporal bone as well as the hammer bone. In this study, it was established the behavioral differences between three different models. This work tries to contribute to tympanic membrane knowledge. The final idea behind this result is to design biomedical devices that can reproduce its performance.